O rokokowej realizacji Tassowego wątku w "Erotykach" Franciszka Dionizego Kniaźnina - Mazurkowa, Bożena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The author devotes attention to four pieces from the poetic cycle Erotics (Erotyki, 1779) of Franciszek Dionizy Kniaźnin, cleary inspired by a few scenes from romantic thread of Tancred and Clorinda in epic poem Godfrey or Jerusalem Delivered (Gofred abo Jeruzalem wyzwolona, 1618) by Tasso‑Kochanowski. The context of consideration are reflections which concern interest in baroque work and characteristic cult of Italian artist, lively in Poland until romanticism. The goal of detailed analysis is to capture multiple signals of connections between Kniaźnin’s rococo lyrics and paralel fragments of seventeenth‑century translation. In the poem’s plot these relations concern meetings of Christian knight with beautiful pagan, his behaviour in these situations, statements which he addressed to both living and departed Clorinda and also the dream in which he was haunted by ghost of the loved woman. Comparative steps aim at determining how epic material was used and processed in the amorous poetry of good taste”.